Growth of PB260’s Bud on Stump GT1 With Treatment Humectants and Plant Growth Regulator - Mila Lukmana; Herry Iswahyudi; Muhammad Helmy Abdillah (Jurnal AGROSAINS dan TEKNOLOGI, 2022)
In increasing latex production, the government recommends the use of superior clones in the form of rubber plant stumps, but the drawback is that vegetative growth is not optimal if the treatment is not appropriate, especially the mortality percentage of buds from budding buds from grafting is quite high due to poor microclimate, poor of nutrients, soil water content and low phytohormones. Therefore, a humectant material that contains nutrients is needed as well as being able to store water properly. Stimulation of vegetative growth can be stimulated by the administration of growth regulators. This study aims to compare the effect of various humectants with the addition of various solutions of growth regulators. The experimental design used a factorial completely randomized design with treatment using solid waste rubber crumbs, solid decanter, and chicken manure as humectants with each dose of 200 g which was doused with a solution of growth regulators, namely coconut water, onion, and leri solution with volume 200 ml per day. The results showed that there was a positive interaction between 200 g crumb rubber solid waste and coconut water solution on the increase in shoot height and the growth of the number of rubber umbrellas. The application of crumb rubber solid waste with leri was able to stimulate the formation of denser leaves. Application of chicken manure with coconut water solution stimulates lateral root growth.